Nationwide carrier screening for congenital adrenal hyperplasia: integrated approach of CYP21A2 pathogenic variant genotyping and comprehensive large gene deletion analysis - Yossawat Suwanlikit; Bhakbhoom Panthan; Pawares Chitayanan; Sommon Klumsathian; Angkana Charoenyingwattana; Wasun Chantratita; Objoon Trachoo (BMC Medical Genomics)
Abstract Background Congenital Adrenal Hyperplasia (CAH) due to 21-hydroxylase deficiency (21-OHD CAH) is an autosomal recessive disorder resulting from pathogenic variants in the CYP21A2 gene. The disorder exhibits variable clinical severity, with the classical form manifesting as salt-wasting crisis in neonates, while inducing ambiguous genitalia in females and precocious puberty in males through simple virilization. Identifying at-risk couples during the preconception stage holds significance for optimizing reproductive choices. Methods: This study included 204 unrelated preconception individuals undergoing carrier screening. A robust molecular approach was devised for rapid detection of nine prevalent CYP21A2 pathogenic variants, utilizing Amplification-Refractory Mutation System (ARMS) PCR and mass spectrometry (MS) genotyping. Complementary quantitative real-time PCR (qPCR) and PCR-based Restriction Fragment Length Polymorphism (PCR-based RFLP) assays were employed for comprehensive gene deletion analysis. The concordance of pathogenic variant detection between ARMS-PCR and MS, as well as the consistency observed in molecular insights from qPCR and PCR-based RFLP, fortified the accuracy of our methodologies. Results: Our combined method could detect common pathogenic variants and large gene deletions with high concordance between ARMS-PCR, MS genotyping, qPCR, and PCR-based RFLP assays. Remarkably, two carriers exhibited significant large-scale deletions, while another manifested a carrier state due to minor-scale gene conversion. The estimated carrier frequency in our cohort using these methods was approximately 1 in 65 individuals. Conclusions: The methods used for 21-OHD CAH carrier screening offer a reliable, swift, and cost-effective approach for detecting common pathogenic variants and large deletions. Despite some limitations, such as the inability to detect all rare mutations, the techniques provide a practical solution for carrier screening, with an estimated carrier frequency of 1 in 65 in our study population. These findings support the potential adoption of these methods in national carrier screening programs, offering a practical balance between efficiency and affordability.